THE INFLUENCE OF JOB STRESS, JOB ROTATION, AND FEEDBACK ON PUBLIC SERVICE MOTIVATION AT SERVICE OFFICE OF STATE PROPERTY AND AUCTION (KPKNL) MANADO - Moningka, Sheila (FEB Universitas Sam Ratulangi Manado, 2014)
Indonesian people has been interested to become civil servant for several years. The data of Civil Servants in Indonesia is more than 4 million, compare to the number of entrepreneurs in the range of 3 million. Being a civil servant is appealing because of the facilities and the retirement security. This view tends to lead to the supposition that the motivation of civil servants is a matter of the materials. This research designed to analyze the influence of internal motivation for public service, which derived from individual aspect in job stress, organization aspect in job rotation and from environment in feedback. This is a quantitative research that associative with multiple linear regression analysis technique. The population in this study is the civil servants at Service Office of State Property and Auction (KPKNL) Manado, whereas the respondents are 37 people. The result of this research shows that there is significant simultaneous and partial influence of Job Stress, Job Rotation and Feedback on Public Service Motivation at Service Office of State Property and Auction Manado. Therefore, organizations should also consider the interests of civil servants in the decision making process and as civil servants to manage time to maximize their work. Keywords: stress, rotation, feedback, motivation